Agro-industrial wastes for biotechnological production as potential substrates to obtain fungal enzymes - Matei, Jéssica Crecencio; Oliveira, João Arthur dos Santos; Pamphile, João Alencar; Polonio, Julio Cesar (Ciência e Natura, 2021)
Agro-industrial wastes contain high moisture content and are rich in nutrients, and can be used as useful substrates by microbes with the supplementation of nitrogen sources, thus providing an alternative tool for the industrial production of many products of economic value, such as enzymes for example. These are proteins that function as biological catalysts, responsible for carrying out various biochemical reactions, being applied in detergent, food, paper and cellulose, cosmetics, textile industries, etc. However, they are expensive raw materials, and it is worth noting that an important part of the cost of manufacturing enzymes is mainly due to the expense of means and fermentation processes. Thus, to minimize the cost of this production and in order to reduce the degradation of the environment due to agricultural waste, a variety of microorganisms and agro-industrial “by-products” can be used to facilitate the economic production of enzymes.Therefore, in this work, a review was carried out on agro-industrial residues and the main enzymes in the industrial market, as well as the use of these materials as sources to obtain enzymes produced by fungi.